NpSe2: a Binary Chalcogenide Containing Modulated Selenide Chains and Ambiguous‐Valent Metal. Issue 45 (24th September 2019) - Jin, Geng Bang; Malliakas, Christos D.; Hu, Yung‐Jin; Booth, Corwin H.; Ibers, James A.; Sokaras, D.; Weng, T.‐C.; Skanthakumar, S.; Soderholm, L.
Abstract : A new binary compound, NpSe2, possesses metal–chalcogen and chalcogen–chalcogen interactions different from those reported for other metal dichalcogenides. Its structure is incommensurately modulated and features linear Se chains and valence‐ambiguous Np cations.